Randomized double-blind placebo-controlled multicenter trial for the effects of a polyherbal remedy, Yokukansan (YiganSan), in smokers with depressive tendencies - Maki Komiyama; Yuka Ozaki; Hiromichi Wada; Hajime Yamakage; Noriko Satoh-Asahara; Akihiro Yasoda; Yoichi Sunagawa; Tatsuya Morimoto; Shinji Tamaki; Masahiro Suzuki; Takuo Shibayama; Toru Kato; et al. (BMC, 2022)
Abstract Background Smoking and depression are closely related and form a vicious cycle. Yokukansan (YiganSan) is a polyherbal remedy that has the effect of calming neuropsychiatric symptoms such as anger and irritation. To examine the efficacy of Yokukansan during smoking cessation (SC) therapy in smokers with depressive tendencies but without major depressive disorders requiring pharmacotherapy. Methods A multicenter, double-blind, randomized, placebo-controlled, parallel-group comparison trial was conducted between June 2016 and May 2020 at 12 centers of the National Hospital Organization, Japan. This trial targeted smokers who first visited the SC outpatient clinics, did not receive any pharmacological treatment at the psychiatric or psychosomatic department, and scored 39 or more on the self-rating depression scale (SDS). Participants (n = 198) were randomly assigned to either the Yokukansan or placebo groups. The trial drug was initiated with the start of the SC treatment and continued for 12 weeks. The primary outcome was the high success rate of the SC treatment, and the secondary outcomes included changes in scores of the SDS and the Profile of Mood States (POMS) instrument. Results The success rate of the SC treatment was similar between the placebo (63%) and Yokukansan (67%) groups (P = .649). The SDS scores (placebo: mean difference [MD] = -3.5, 95% confidence interval [CI][-5.8, -1.2], d = 0.42; Yokukansan: MD = -4.6, 95%CI[-6.8, -2.3], d = 0.55), and the "tension-anxiety" POMS-subscale scores (placebo: MD = -1.6, 95%CI[-2.5, -0.7], d = 0.52; Yokukansan: MD = -1.6, 95%CI[-2.9, -0.3], d = 0.36) showed significant improvement in both groups after the SC treatment. However, "depression-dejection" improved in the Yokukansan group (MD = -1.9, 95%CI[-3.1, -0.7], d = 0.44) but not in the placebo group (MD = -0.1, 95%CI[-1.0, 0.7], d = 0.04). Significant improvement in "fatigue" was noted in the Yokukansan group (MD = -2.1, 95%CI[-3.4, -0.9], d = 0.47) but not in the placebo group (MD = -0.5, 95%CI[-1.8, 0.8], d = 0.11). The time × group interaction on the improvement in "depression-dejection" was significant (P = .019). Conclusions Yokukansan does not increase the SC treatment's success rate but has additional positive effects on the psychological states due to the SC treatment in smokers with depressive tendencies but without apparent mental disorders. Trial registration ID: UMIN000027036. Retrospectively registered at UMIN on April 18, 2017.